Government auditing and corruption control: Evidence from China's provincial panel data - Jin Liu; Bin Lin (China Journal of Accounting Research, 2012)
Since its foundation, China's government auditing system has played a very important role in maintaining financial and economic order and improving government accountability and transparency. Though a great deal of research has discussed the role of government auditing in discovering and deterring corruption, there is little empirical evidence on whether government auditing actually helps to reduce corruption. Using China's provincial panel data from 1999 to 2008, this paper empirically examines the role of government auditing in China's corruption control initiatives. Our findings indicate that the number of irregularities detected in government auditing is positively related to the corruption level in that province, which means the more severe the corruption is in a province, the more irregularities in government accounts are found by local audit institutions. Also, post-audit rectification effort is negatively related to the corruption level in that province, indicating that greater rectification effort is associated with less corruption. This paper provides empirical evidence on how government auditing can contribute to curbing corruption, which is also helpful for understanding the role of China's local audit institutions in government governance and can enrich the literature on both government auditing and corruption control.
Keywords: D73; G38; M42; 650; Government auditing; Post-audit rectification; Corruption control